The Long-Run and Gender-Equalizing Impacts of School Access: Evidence from the First Indochina War - Hai-Anh H. Dang; Trung X. Hoang; Ha Nguyen (Global Labor Organization (GLO), 2018)
Very few studies currently exist on the long-term impacts of schooling policies in developing countries. We examine the impacts—half a century later—of a mass education program conducted by the Democratic Republic of Vietnam in the occupied areas during the First Indochina War. Difference-in-difference estimation results suggest that school-age children who were exposed to the program obtained significantly higher levels of education than their peers who were residing in French-occupied areas. The impacts are statistically significant for school-age girls and not for school-age boys. We find beneficial spillover and inter-generational impacts of education: affected girls enjoyed higher household living standards, had more educated spouses, and raised more educated children. We discuss various robustness checks and extensions that support these findings.
Keywords: H0; I2; O1; P3; 330; education achievement; reading literacy; school policy; popular education; difference-in-difference; long-term impact; war